2015
DOI: 10.1016/j.kjms.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Standard percutaneous nephrolithotomy alone versus in combination with intraoperative anterograde flexible nephroscopy for staghorn stones: A retrospective study

Abstract: This study aimed to compare the outcomes of standard percutaneous nephrolithotomy (PCNL) to PCNL with intraoperative antegrade flexible nephroscopy (IAFN) for treating stones of staghorn nature. We retrospectively analyzed patients treated using PCNL between January 2007 and July 2013. A total of 1250 patients were treated using PCNL, and 166 patients had staghorn stones. All patients had been subjected to a complete blood count, routine biochemical analyses, coagulation tests, a complete urine analysis, and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In pediatric patients, this achieved a stone-free rate of 87% in these difficult-to-treat cases because of the small size of the calyx [17], and in adult patients there was a 92% stone-free rate compared to 80% in patients treated with flexible URS alone [18]. Large stones treated in adults achieved a 81.7% stone-free rate versus 38.9% for mini-PCNL alone [19]; however, the stone-free rates for staghorn stones were similarly high, above 85%, for patients treated with PCNL alone and PCNL and flexible URS in combination, and the combination treatment was longer, with a longer hospitalization time, but this method used traditional PCNL [20]. Other combined methods that used some form of miniaturized PCNL showed shorter operation times than the isolated procedures [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In pediatric patients, this achieved a stone-free rate of 87% in these difficult-to-treat cases because of the small size of the calyx [17], and in adult patients there was a 92% stone-free rate compared to 80% in patients treated with flexible URS alone [18]. Large stones treated in adults achieved a 81.7% stone-free rate versus 38.9% for mini-PCNL alone [19]; however, the stone-free rates for staghorn stones were similarly high, above 85%, for patients treated with PCNL alone and PCNL and flexible URS in combination, and the combination treatment was longer, with a longer hospitalization time, but this method used traditional PCNL [20]. Other combined methods that used some form of miniaturized PCNL showed shorter operation times than the isolated procedures [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, these techniques cannot resolve all cases with multiple kidney stones, resulting in a low stone-free rate and complications in some patients [12,14]. Previous reports have demonstrated that miniaturized PCNL combined with digital flexible URS is safe for pediatric [17] and adult patients [18] with multiple kidney stones and for adults with large stones [19,20]. The combination of SMP and flexible URS means the entire procedure from puncture to PCNL can be constantly monitored and limits the size and number of tracts during PCNL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stone free rate was 87% with flexible nephroscopy vs. 81% without it. 13 In a similar study by Desai et al, a retrospective analysis of 684 patients who underwent PCNL with multiple tracts or PCNL with flexible nephroscopy through single tract. They found no difference in stone free rate among both groups.…”
Section: Discussionmentioning
confidence: 99%
“…They had mean operating time of 95 and 113 minutes for standard PCNL and PCNL with flexible nephroscopy respectively. 13 …”
Section: Discussionmentioning
confidence: 99%